KPI-Based Performance Appraisal and Employee Salary Increase Decisions: A Qualitative Study at PT Sucorinvest Asset Management Jakarta - Hilman Hidayat; Ratnawati Prayogi; Bambang Rismadi; Dwi Novita Sari (International Journal of Management Science and Information Technology, 2026)
This study aims to analyze the implementation of Key Performance Indicators (KPI) as a basis for determining employee salary increases at PT Sucorinvest Asset Management, Jakarta. Effective human resource management requires an objective performance measurement system to ensure that employee contributions are aligned with organizational goals and compensation policies. In this context, KPI serves as a strategic tool for measuring employee performance through measurable indicators and supporting managerial decision-making related to remuneration. This study employed a descriptive qualitative approach. Data were collected through in-depth interviews, observations, and documentation involving seven informants representing managerial and operational levels within the organization. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing. The findings indicate that the company has implemented a KPI system based on the Balanced Scorecard approach, integrating financial, customer, internal process, and learning and growth perspectives into employee performance evaluation. KPI has been utilized as an important reference for salary increase decisions and performance monitoring. However, several challenges were identified, including inconsistent KPI socialization among employees, limited transparency in the conversion of KPI scores into salary increase percentages, variations in KPI monitoring practices across divisions, and the influence of external business conditions on KPI target achievement. These issues affect employees’ understanding and perceptions of fairness regarding the performance evaluation process. The study concludes that KPI provides a structured framework for performance appraisal and supports more objective salary increase decision-making. The findings highlight the importance of consistent KPI communication, greater transparency in remuneration mechanisms, and adaptive performance targets to enhance the effectiveness of KPI-based performance management systems.